PUSAT PEMULIHAN KORBAN TINDAK KEKERASAN TERHADAP PEREMPUAN DENGAN PENERAPAN METODE TERAPI KOGNITIF PERILAKU DI JAKARTA - Kerin Christine Oktoria; Sumaryoto Sumaryoto; Rachmadi Nugroho (Universitas Sebelas Maret Surakarta, 2015)
Violence against women often happens in various regions in Indonesia, especially in Jakarta. This is exacerbated by the lack of infrastructure that provides a wide range of facilities to handle and prevent acts of violence. This phenomenon needs a recovery center that can accommodate a series of processes to return the original condition of the victims that include therapeutic activities, restoration of social interaction between individuals, training of various skills, as well as provide education and information related to violence and its prevention, is needed. The problem is how to design the site, space, material and color, composition and layout of the building, and landscaping at the recovery center that can support the sustainability of recovery process through the application of methods of Cognitive Behavioral Therapy. The method used is based on the architectural design characteristics obtained from the application of Cognitive Behavioral Therapy methods in object design. The result obtained is the design of a recovery center for victims of violence against women, ranging from the treatment, education and development, and housing that reflects the application of Cognitive Behavioral Therapy method as a method of recovery. Keywords: Acts of Violence, Women, Psychology Aspect, Cognitive Behavioral Therapy